Disabling forensic mental health detention: the carcerality of the disabled body - Steele, Linda (Punishment & society, 2017)
“Disabling” forensic detention involves challenging the self-evidence of the meaning of disability in forensic mental health law, and in turn illuminating the significance of this meaning to the possibility and permissibility of forensic detention and other interventions in the bodies of people designated with cognitive impairments and psychosocial disabilities (“people designated as disabled”). I apply this approach to an examination of a case study of one individual subjected to forensic detention: an Indigenous Australian woman with Fetal Alcohol Spectrum Disorder, Roseanne Fulton. By examining Fulton’s forensic detention, in the context of her earlier life circumstances and her subsequent journey through various “alternatives” to this forensic detention I show the interrelationships of forensic detention with a range of legal options for punishing, regulating and intervening in designated as disabled bodies and situate these interrelationships in a broader range of issues of violence, institutional failure, social disadvantage, settler colonialism, and ableism. My central argument is that the ongoing subjection of Fulton to a range of forms of control across her life suggest that the possibility of forensic detention and other forms of punishment of people designated as disabled is not attached to a particular material architectural space or a particular court order, but instead attaches to these individuals’ bodies via medico-legal designations as disabled and travels with these individuals through time and space. I propose that more directly it is the disabled body that is the space of punishment and the disabled body makes material architectural spaces punitive. A “reform”, indeed even an “abolition”, approach focused on material architectural spaces of disabled punishment will not interrupt the ongoing processes of control of criminalized people designated as disabled if it does not also acknowledge and challenge the temporal and carnal logics underpinning the carcerality of the disabled body itself.